An Aminobutyric Acid Transaminase in Zea mays Interacts With Rhizoctonia solani Cellulase to Participate in Disease Resistance - Guo, Xiuna; Chen, Jinyin; Gao, Mengyi; Li, Duochuan (Frontiers in Plant Science, 2022)
Corn sheath blight, caused by AG1-IA, a fusion group of Rhizoctonia solani, which acts as a kind of necrotrophic fungal pathogen, poses a global tremendous threat to the production of Zea mays. Although cellulase plays a crucial role in Rhizoctonia solani infections, how plants respond to it is still poorly understood. In this study, we identified a gamma-aminobutyric acid transaminase (GABA-T), ZmGABA-T, in Zea mays that interacts with a cell wall-degrading enzyme (CWDE), EG1, in the cell membrane, using yeast two-hybrid assay, co-immunoprecipitation (Co-IP), and bimolecular fluorescence complementation (BiFC) assays. We found that the combination of EG1 and ZmGABA-T suppressed the allergic necrosis induced by EG1. We also found that the substrate of GABA-T--GABA, can inhibit the transcription of EG1. Transient expression of ZmGABA-T inhibited Rhizoctonia solani infection in Nicotiana benthamiana. The homologue in Oryza sativa, OsGABA-T, could also interacted with EG1 to suppress the allergic necrosis induced by EG1. The OsGABA-T knocked out plants displayed enhanced susceptibility to Rhizoctonia solani and showed more larger lesions. In conclusion, our results suggest that ZmGABA-T inhibits allergic necrosis induced by EG1 based on the combination with EG1, producing resistance to Rhizoctonia solani infection.